2017
DOI: 10.12937/ejsise.16.18
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Graded Response Model of Item Response Theory to Computerized Dynamic Assessment in L2 English Education

Abstract: The purposes of this paper are to (a) develop an adaptive system with the help of the graded response model of IRT, (b) test the system with a small group of L2 learners, (c) examine the feasibility of computerized dynamic assessment, and (d) propose a new set of scoring mechanisms. We developed a computer-based adaptive system that provides students with appropriate test items and a set of graduated prompts from implicit to explicit under the conditions of mediation. We found that the set of graduated prompts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They also identified key markers that could be used for data analysis. Sumi and Miyazawa (2017) suggested that effective scaffolding for English language learners involves predicting the level of support needed to complete tasks and determining the appropriate level of help to facilitate learners' development. X. proposed a hybrid design of English teaching methodology courses guided by constructivist theory, and reported the corresponding norms and learner performance outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…They also identified key markers that could be used for data analysis. Sumi and Miyazawa (2017) suggested that effective scaffolding for English language learners involves predicting the level of support needed to complete tasks and determining the appropriate level of help to facilitate learners' development. X. proposed a hybrid design of English teaching methodology courses guided by constructivist theory, and reported the corresponding norms and learner performance outcomes.…”
Section: Introductionmentioning
confidence: 99%